Does Hypothyroidism Affect Post-Operative Outcome of Patients Undergoing Carpal Tunnel Release? - Sharareh Roshanzamir; Sahameddin Mortazavi; Alireza Dabbaghmanesh (Electronic Physician, 2016)
Introduction: Risk factors associated with Carpal Tunnel Syndrome include repetitive use of hand and wrist, advanced age, obesity, pregnancy, diabetes mellitus and thyroid disease. Decompression of the median nerve is the last treatment of choice usually indicated when negative results to conservative treatments remain for three months. In this study, we aimed to find out whether hypothyroid patients would respond to CTS surgical decompression differently in comparison to healthy individuals. Methods: This case control study was conducted on patients with CTS in need of surgical release who were refered to Shahid Faghihi hospital, International Branch of Shiraz University of Medical Sciences, Shiraz, Iran from January 2013 to January 2015. Twenty-five hypothyroid and 22 euthyroid patients were recruited. Hypothyroidism was diagnosed based on clinical symptoms and serum TSH level. All patients were followed for three weeks after surgery and a Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) was completed for them pre and post operation. An electrophysiological study was performed during the same follow up period. Statistical analysis was performed using SPSS version 16. Results: The CTS grade reported by electrophysiological study, decreased significantly 3 weeks after operation in comparison with preoperative grades (p<0.001). A significant decrease was observed in the immediate postoperative BCTQ scores compared to preoperative (p<0.001). Also a decrease was detected in the three weeks of postoperative follow up compared to immediate postoperative BCTQ scores (p<0.001) and preoperative BCTQ scores (p<0.001). Postoperative BCTQ scores of euthyroid patients decreased more in comparison to hypothyroid patients (p<0.001). Conclusion: It seems that, hypothyroidism has an effect on postoperative outcome of carpal tunnel release.